Health Effects of Chronic Arsenic Exposure - Young-Seoub Hong; Ki-Hoon Song; Jin-Yong Chung (Korean Society for Preventive Medicine, 2014)
Arsenic is a unique element with distinct physical characteristics and toxicity whose importance in public health is well recognized. The toxicity of arsenic varies across its different forms. While the carcinogenicity of arsenic has been confirmed, the mechanisms behind the diseases occurring after acute or chronic exposure to arsenic are not well understood. Inorganic arsenic has been confirmed as a human carcinogen that can induce skin, lung, and bladder cancer. There are also reports of its significant association to liver, prostate, and bladder cancer. Recent studies have also suggested a relationship with diabetes, neurological effects, cardiac disorders, and reproductive organs, but further studies are required to confirm these associations. The majority of research to date has examined cancer incidence after a high exposure to high concentrations of arsenic. However, numerous studies have reported various health effects caused by chronic exposure to low concentrations of arsenic. An assessment of the health effects to arsenic exposure has never been performed in the South Korean population; thus, objective estimates of exposure levels are needed. Data should be collected on the biological exposure level for the total arsenic concentration, and individual arsenic concentration by species. In South Korea, we believe that biological exposure assessment should be the first step, followed by regular health effect assessments.